Advances in the physiology of gastric emptying. Issue 4 (10th February 2019) - Goyal, Raj K.; Guo, Yanmei; Mashimo, Hiroshi
Abstract: There have been many recent advances in the understanding of various aspects of the physiology of gastric motility and gastric emptying. Earlier studies had discovered the remarkable ability of the stomach to regulate the timing and rate of emptying of ingested food constituents and the underlying motor activity. Recent studies have shown that two parallel neural circuits, the gastric inhibitory vagal motor circuit (GIVMC) and the gastric excitatory vagal motor circuit (GEVMC), mediate gastric inhibition and excitation and therefore the rate of gastric emptying. The GIVMC includes preganglionic cholinergic neurons in the DMV and the postganglionic inhibitory neurons in the myenteric plexus that act by releasing nitric oxide, ATP, and peptide VIP. The GEVMC includes distinct gastric excitatory preganglionic cholinergic neurons in the DMV and postganglionic excitatory cholinergic neurons in the myenteric plexus. Smooth muscle is the final target of these circuits. The role of the intramuscular interstitial cells of Cajal in neuromuscular transmission remains debatable. The two motor circuits are differentially regulated by different sets of neurons in the NTS and vagal afferents. In the digestive period, many hormones including cholecystokinin and GLP‐1 inhibit gastric emptying via the GIVMC, and in the inter‐digestive period, hormones ghrelin and motilin hasten gastric emptying by stimulating the GEVMC. The GIVMC and GEVMC are also connected to anorexigenic and orexigenic neural pathways, respectively. Identification of the control circuits of gastric emptying may provide better delineation of the pathophysiology of abnormal gastric emptying and its relationship to satiety signals and food intake. Abstract : Identification of the control circuits of gastric emptying may provide better delineation of the pathophysiology of abnormal gastric emptying and its relationship to satiety signals and food intake.